2021
DOI: 10.1038/s41581-021-00454-y
|View full text |Cite
|
Sign up to set email alerts
|

Pro-resolving lipid mediators: regulators of inflammation, metabolism and kidney function

Abstract: An inflammatory response arising in the absence of a pathogen (for example, toxin exposure, mechanical tissue injury and ischaemia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 202 publications
(242 reference statements)
1
73
0
Order By: Relevance
“…Numerous hard-to-treat disorders, including cardiovascular disease, diabetes, and neurological issues, have been intimately connected with uncontrolled inflammation [ 32 ]. Emerging evidence suggests the pivotal role of specific lipid mediators in modulating inflammation resolution [ 33 ]. The present study showed that the DHA products RvD1 and PD1 reduce CaOx deposition by alleviating the ROS-induced inflammatory response, providing strong evidence for the inhibitory effect of active lipid components on inflammation and expanding our understanding of the role of lipid components in inflammation regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous hard-to-treat disorders, including cardiovascular disease, diabetes, and neurological issues, have been intimately connected with uncontrolled inflammation [ 32 ]. Emerging evidence suggests the pivotal role of specific lipid mediators in modulating inflammation resolution [ 33 ]. The present study showed that the DHA products RvD1 and PD1 reduce CaOx deposition by alleviating the ROS-induced inflammatory response, providing strong evidence for the inhibitory effect of active lipid components on inflammation and expanding our understanding of the role of lipid components in inflammation regulation.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Obesity, diabetes mellitus, hypertension, and cardiovascular disease are believed to be among the underlying conditions that give rise to the low‐grade inflammation that impairs insulin signaling. 37 Several studies have also noted an association between CKD‐induced insulin resistance and muscle protein wasting. 4 , 38 Protein degradation is increased with CKD‐associated insulin resistance, and therefore, it is difficult to manage protein intake in these patients, especially those on a low‐protein diet.…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial reported that local topical treatment of gingival inflammation with a proresolving lipoxin/resolvin stable analog is safe and effective as well as activated endogenous production of SPMs present in peripheral blood [ 63 ]. A new generation of lipoxin stable analog mimetics introduced by investigators in Dublin hold exceptional promise for novel pro-resolving treatments in inflammation-resolution for kidney diseases and the many diabetic complications [ [64] , [65] , [66] ]. They demonstrated with analyses of nasal lavages that SPMs, e.g., RvD2, are dysregulated in human rhinosinusitis.…”
Section: Spms In Covid-19 Infections and Other Human Studiesmentioning
confidence: 99%